دور قانون الموازنة العراقية في النهوض بالواقع الاقتصادي-دراسة تحليلية تطبيقية في ضوء قانون الموازنة العراقي لسنة 2023 - نايف وسن حميد زاطي (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The General Budget is a statement report that the Executive expects to spend or collect from amounts during a separate financial period, often a year. and called the fiscal year, there are many factors that lead to imbalance in the application of the budget including the modernization of the Iraqi economic system, as well as Iraq’s suffering from the wars that have accumulated and continued to affect the country’s economy for years. as well as weak private sector support and public sector budgetary focus, This has led to a decline in service levels, and the adoption of the Iraqi general budget on oil revenues by over 80% is a risk factor for Iraq’s economy and growth. Border crossings contribute a small proportion to the State’s revenues, transforming the country into a consumer country, thus slowing growth rates.